Application of Monte Carlo Simulation and PERT/CPM Techniques in the Construction Project Planning of PLTMG Ambon-2 - Ibrahim, Wahyu Sugar (Syntax Literate, 2025)
Construction project scheduling and monitoring pose significant challenges in today’s dynamic business environment. This study investigates the implementation of two widely used project management techniques - the Critical Path Method (CPM) and the Project Evaluation and Review Technique (PERT) - in combination with Monte Carlo simulation for risk-based planning. The case study focuses on the PLTMG (Gas Engine Power Plant) Ambon-2 project. CPM provides a deterministic schedule with an estimated completion time of 65 weeks, representing an optimistic scenario. In contrast, the Monte Carlo simulation incorporates uncertainty and risk factors, indicating a 56.98% probability of project completion within 76 weeks and a 43.02% risk of delay. The results demonstrate the limitations of deterministic methods in high-risk environments and highlight the advantages of probabilistic simulations for more realistic project forecasting.